2011
DOI: 10.1103/physrevb.84.054441
|View full text |Cite
|
Sign up to set email alerts
|

Defect-trapped electrons and ferromagnetic exchange in ZnO

Abstract: A model for ferromagnetism observed at ambient temperature in films of oxides such as ZnO is proposed and evaluated. The ferromagnetic moment in the model arises from electrons trapped at negatively charged vacancies in an n-type oxide. These vacancies are capable of trapping either one or two electrons. Trapped electrons are described by a one-band Hubbard Hamiltonian where the Hubbard U is the effective electron-electron repulsion for a pair of electrons in a vacancy. Ferromagnetism is known to exist in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 90 publications
3
33
0
Order By: Relevance
“…It can be interpreted as an evidence that the magnetic order development is related to the presence of vacancies, such as V Zn , in the crystal lattice of the Zn nanoparticles, whose role in RTFM was reported earlier for undoped ZnO [80,81]. ܸ For magnetization to reach a value comparable to those observed in the our experiments, the defect density in the order of 1 at % was necessary in ZnO [25]. This was found comparable to the decrease in V observed in our NPs.…”
Section: Magnetic Measurementssupporting
confidence: 58%
See 2 more Smart Citations
“…It can be interpreted as an evidence that the magnetic order development is related to the presence of vacancies, such as V Zn , in the crystal lattice of the Zn nanoparticles, whose role in RTFM was reported earlier for undoped ZnO [80,81]. ܸ For magnetization to reach a value comparable to those observed in the our experiments, the defect density in the order of 1 at % was necessary in ZnO [25]. This was found comparable to the decrease in V observed in our NPs.…”
Section: Magnetic Measurementssupporting
confidence: 58%
“…For the Zn-O system, also known as a pristine oxide, it was shown that defects, such as Zn and O vacancies [16][17][18][19][20][21], Zn interstitials [22], grain boundaries [23] and lattice distortions [24], might contribute to the development of RTFM. If all these defects are indeed responsible for the ferromagnetism in thin films and nanoparticles, they should be thermodynamically stable at least to room temperature, and magnetic exchange interaction between them should be strong enough for the existence of ferromagnetism to be feasible [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For ease of comparison of TL for both acceptor and donor defects, we refer acceptor levels to the VBM rather than the CBM using the band gap energy, E g , obtained from the ionization potential and electron affinity of the bulk supercell. 7 A TL is denoted (q /q), where q and q are two different charge states of the defect, and is obtained from the difference in formation energies of a defect in two distinct charge states using Eq. (1),…”
Section: Formation Energies and Transition Levelsmentioning
confidence: 99%
“…The values of IP and EA for ZnO are 7.14 eV and 11.06 eV (Ref. 7) from differences in total energies of charged and neutral bulk 3 × 3 × 3 supercells. The absolute IP and EA values have no meaning since they are obtained using charged unit cells.…”
Section: Formation Energies and Transition Levelsmentioning
confidence: 99%